Penerapan Sekolah Ramah Anak Dalam Menanamkan Komunikasi Efektif Peserta Didik dan Guru di Sekolah Dasar - Heri Irawan; Meila Rizka Rahmawati; Berliana Aventina Kavita Ayudia Devani; Muhammad Nofan Zulfahmi (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This study aims to analyze the implementation of child-friendly schools at the elementary school level, as a form of instilling effective communication between students and teachers. The method used in this study is a literature study by reviewing several scientific sources, journals, and articles. The implementation of child-friendly schools is a program that is aligned by the government in order to help with problems in the world of education so that a pleasant learning and teaching situation is created in the classroom. The results of the study show that implementing child-friendly schools can improve effective communication between teachers and students. This study shows the importance of implementing child-friendly schools as an effort to improve effective communication between teachers and students as a support for an exciting and enjoyable learning process.